LukS-PV Induces Apoptosis via the SET8-H4K20me1-PIK3CB Axis in Human Acute Myeloid Leukemia Cells - Xu, Liang Fei; Shi, Lan; Zhang, Shan Shan; Ding, Peng Sheng; Ma, Fan; Song, Kai Di; Qiang, Ping; Chang, Wen Jiao; Dai, Yuan Yuan; Mei, Yi De; Ma, Xiao Ling (Frontiers in Oncology, 2021)
Evidence suggests that histone modification disorders are involved in leukemia pathogenesis. We previously reported that LukS-PV, a component of Panton–Valentine leukocidin (PVL), has antileukemia activities that can induce differentiation, increase apoptosis, and inhibit proliferation of acute myeloid leukemia (AML) cells. Furthermore, LukS-PV inhibited hepatoma progression by regulating histone deacetylation, speculating that LukS-PV may exert antileukemia activity by targeting histone modification regulators. In this study, the results showed that LukS-PV induced apoptosis by downregulating the methyltransferase SET8 and its target histone H4 monomethylated at Lys 20 (H4K20me1). Furthermore, chromatin immunoprecipitation sequencing and polymerase chain reaction identified the kinase PIK3CB as a downstream target gene for apoptosis mediated by SET8/H4K20me1. Finally, our results indicated that LukS-PV induced apoptosis via the PIK3CB-AKT-FOXO1 signaling pathway by targeting SET8. This study indicates that SET8 downregulation is one of the mechanisms by which LukS-PV induces apoptosis in AML cells, suggesting that SET8 may be a potential therapeutic target for AML. Furthermore, LukS-PV may be a drug candidate for the treatment of AML that targets epigenetic modifications.